Assessment of lithium ingestion on cognition and some subset of motor skill - P D Shallie; H B Akpan; A K Adefule; D Fakoya; T R Fagbohun (Wolters Kluwer Medknow Publications, 2010)
Background : Patients taking lithium often report of difficulties in concentration, memory, learning, and attention. Laboratory tests of cognitive functions in healthy volunteers on chronic lithium demonstrate that disruptions in memory-learning processes are apparent at the time of memory retrieval. Aim : This study has attempted to evaluate the impact of lithium ingestion on cognition and some subset of sensory skill, by examining comparatively how lithium or a lithium / saline supplement either harms or helps the brain. Materials and Methods : Wistar Rats (male and female) were housed in individual improvised cages. The rats were acclimatized for two weeks after which they were randomly grouped into three, namely, control, lithium-treated, and lithium with saline-treated groups, and treated for four weeks. The lithium-treated group received 40 mM lithium bicarbonate per kg of feed for the first one week, and the dosage was increased to 60mM per kg of feed for the rest of the three weeks. The lithium-saline group received saline solution in addition to lithium. The control group was given normal feed and water liberally for the period of the experiment. The rats were subjected to a cognitive test using the Barnes maze, assessments of negative geotaxis, cliff avoidance, and some neurotransmitters (acetylcholine and glutamate). The data were analyzed by Microsoft excel 2007. Results : This study shows that lithium ingestion is characterized by a significant ( P ≤ 0.05) decline in learning and memory as compared to the control. While the lithium-saline-treated animals exhibit enhanced cognitive ability. The subset of sensory activity was assessed; negative geotaxis and cliff avoidance were grossly compromised, thus lithium carbonate appeared to have definite negative effects on the psychsensory speed. Conclusion : In conclusion lithium should be co-administered with saline to counter the detrimental effects of lithium noticed in this study, which include impairment of tasks on psychomotor speed and cognition.